Tradisi Tetesan: Pemaknaan Pro-Kontra Terhadap Tradisi Khitan Perempuan Di Kampung Budaya “Kelurahan Patehan” Yogyakarta - Pamungkas, Jati (JOM, 2025)
This study describes the Tetesan tradition in Javanese culture which is carried out in the Patehan village, Yogyakarta. The Tetesan tradition itself is female circumcision for Javanese people in the Yogyakarta Palace environment. This research explains the phenomenon of people who carry out leaving the Tetesan tradition for their daughters. The purpose of this study is to find out the reasons why people carry out the Tetesan tradition and the reasons for people who abandon the Tetesan tradition This research uses field research methodology. The result of this study is that it is known that the people of Patehan village continue to carry out the tradition of female circumcision or circumcision because they preserve the ancestral heritage and the Tetesan tradition is believed to bring goodness to their daughters in adolescence or adulthood. For the people of Patehan village who do not carry out the Tetesan tradition, the reason is because the Tetesan tradition is no longer relevant to current developments and there is no strong religious foundation regarding the Tetesan tradition.